2017
DOI: 10.1007/s00264-017-3546-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for greater trochanteric pain syndrome after total hip replacement confers a poor outcome

Abstract: Purpose Surgery for greater trochanteric pain syndrome (GTPS) may be indicated for cases refractory to conservative measures. We aim to evaluate patient reported outcomes and adverse events following surgery. Methods Postal questionnaires were used to evaluate a consecutive series of 61 bursectomy and gluteal fascia transposition (GFT) procedures. Study outcomes were Oxford hip score, satisfaction score, visual analogue score, pain lying on the affected side, and the duration of pain relief after surgery. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In addition, the results of Robertson-Watres et al showed a poor outcome for patients with surgical treatment for greater trochanteric pain syndrome after THA, analyzing patient satisfaction score; 10 cm visual analogue score referring to current level of pain (0-100, 0 representing no pain); Oxford hip score; Likert scale duration of pain relief following the operation; Binary presence of pain when lying on affected side 8 . This confirms the importance of accurate three-dimensional restoration of the hip joint biomechanics and shows the necessity to prevent this complication already during the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results of Robertson-Watres et al showed a poor outcome for patients with surgical treatment for greater trochanteric pain syndrome after THA, analyzing patient satisfaction score; 10 cm visual analogue score referring to current level of pain (0-100, 0 representing no pain); Oxford hip score; Likert scale duration of pain relief following the operation; Binary presence of pain when lying on affected side 8 . This confirms the importance of accurate three-dimensional restoration of the hip joint biomechanics and shows the necessity to prevent this complication already during the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition MRI analysis show peritrochanteric lesion in over 30% [4][5][6] . Following total hip arthroplasty (THA) 4-17% of patients report these symptoms according to previous studies [7][8][9][10][11] . The reasons of trochanteric pain syndrome as reported in previous studies are manifold and include tendinopathy or microtrauma of the gluteus medius and minimus tendons, often without signs of inflammation 12,13 .…”
mentioning
confidence: 99%
“…In patients with GTPS after total hip arthroplasty, however, outcomes following bursectomy are significantly less favorable than in patients with idiopathic GTPS. 66 , 67 Robertson-Waters et al 66 found that only 18% of patients experienced sustained pain relief at median 34-month follow-up and 22% experienced no improvement at all. The authors reported a reoperation rate of 11% and a complication rate of 13%, including one patient who developed a postoperative wound infection that progressed to a periprosthetic joint infection.…”
Section: Operative Managementmentioning
confidence: 99%
“…These 56 patients have been reported in a previous study that evaluated patient-reported outcomes following trochanteric bursectomy and transposition of the gluteal fascia. 9 The patients in this previous study were diagnosed with GTPS based on clinical history and greater trochanteric tenderness. They all underwent surgery when symptoms had persisted for over 12 months and a transient response to conservative measures, including corticosteroid injection and physiotherapy, was observed.…”
Section: Methodsmentioning
confidence: 99%